Farming with alternative pollinators for increased biodiversity and smallholder incomes in Zimbabwe - Allebone-Webb, Sophie; Gossrau, Felix; Orland, Chloé; Bara, Gracian Takudzwa; Fioekou, Cédric; Matsika, Annah; Riber, Karl; Mahaman Dioula, Bader (Frontiers in Agronomy, 2025)
Pollinator populations have dramatically declined over the past 50 years, with over 40% of invertebrate pollinator species at risk of extinction largely due to intensive agriculture, pesticide use, habitat loss and climate change. Pollinators provide an essential ecosystem service, with about 75% of global crops relying on pollination by animals. It is therefore essential to reconsider conventional farming practices, which are largely responsible for this decline. By cultivating flowering crops known as “Marketable Habitat Enhancement Plants”, (MHEPs), alongside the edges of pesticide-free fields, the Farming with Alternative Pollinators (FAP) approach aims to enhance the presence of wild pollinators. In this study, we compared the performance of a total of 43 smallholder farmer plots using the FAP approach with plots following conventional approaches, for pollinator abundance and diversity, and for yield and income in Zimbabwe. We found significantly higher pollinator abundance and richness in FAP plots compared to control plots. There was significantly higher income and higher value of yields for all offtake in FAP plots for both crop cycles measured. Plots with higher pollinator abundance showed significantly higher income from all crops and significantly higher value of yields, showing a clear link between pollinator populations, crop production and income.